Investigating the relationship between fear of missing out and teacher education students' school engagement in physical education - Ishak, Muchamad; Yunisal, Papat; Setiawan, Edi; Fernando, Leanjo; Lobo, Joseph (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: Notably, there is a scarcity of papers that focus on deepening the relationship between fear of missing out (FoMO) and school engagement for undergraduate students, most especially in a university setting in Indonesia and the Philippines. Research Objectives: In this regard, this study aims to deepen the relationship between the FoMO and school engagement. Methods: In this research, a correlational method was adopted. The respondents for the study were undergraduate students currently taking the Bachelor of Physical Education degree at the College of Teacher Training and Education Pasundan (Indonesia) and the University in Region III (Philippines). Instrument FoMO used the Fear of Missing Out scale (FoMOS), and the involvement used UWES-9. Pearson-R analysis was used to analyse the relationship between FoMO and school engagement. Finding/Results: After obtaining data from 100 teacher education students taking the degree in Bachelor of Physical Education, it was observed that there is no significant relationship between overall FoMO and school engagement (r(98) = .190, p = .059). Additionally, no significant relationship was found between the FoMO-Private Factor (r(98) = .145, p = .147), the FoMO-Social Factor (r(98) = .173, p = .085), and school engagement. Conclusion: Thus, we confirm that students' engagement in their studies is not significantly influenced by FoMO. This research contributes information to teachers and students regarding the relationship between FoMO and school engagement in physical education.